(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The main objective of the study was to determine the perception and knowledge of yam farmers on COVID-19 pandemic in Taraba State. A total of 120 respondents were purposively selected from 8 village communities of 4 local government areas of the state. The local government areas were: Wukari, Ibbi, Yorro and Zing. Data were collected on perception of farmers on COVID-19 pandemic, knowledge of yam farmers on COVID-19 disease and farmers source of information on COVID-19 pandemic. Data collected were presented using frequency and percentages, mean score and standard deviation. The result of the analysis revealed that the respondents perceived that COVID-19 pandemic poses danger to livelihood (=3.79), COVID-19 pandemic exists (=3.54), COVID-19 pandemic is contagious (=3.48) and COVID-19 pandemic brought health complications to farmers (=3.47). Respondents had good knowledge of COVID-19 pandemic as the majority (76.7%) know that maintaining social distance can prevent COVID-19 infection, about 76% were aware that COVID-19 is a contagious disease and 74.2% were knowledgeable that hand washing with soap on a regular basis can help to prevent COVID-19 infection. Respondents had multiple sources of information on COVID-19 pandemic as all (100%) of the farmers cited radio as a source of their information on COVID-19 pandemic, 90.8% rely on family members and 90% rely on friends as a source of their information on COVID-19 pandemic. It was recommended that government should establishing institutional frameworks, policies and procedures for pandemic preparedness and response.